Novel application of in vivo micro-optical coherence tomography to assess cornea scarring in an animal model - Ang, Marcus (2018)
This pilot study uses a micro-optical coherence tomography (micro-OCT) system with ~1 μm axial resolution specifically to image the cornea and corneal scars in vivo. We used an established murine corneal scar model by irregular phototherapeutic keratectomy in ten C57BL/6 mice, with serial imaging using the micro-OCT and compared to anterior segment (AS-OCT) (RTvue, Optovue, Fremont, CA) before and after scar induction. Main outcome was agreement between the AS-OCT and micro-OCT using Bland-Altman plots (95% limits of agreement, LoA).We analysed 10 control eyes and 10 eyes with corneal scars and found that there was good agreement between AS-OCT and micro-OCT (P > 0.05) LOA: lower limit −14 µm (95% CI: −19 to −8.8 µm) upper limit 23 µm (95% CI: 18 to 28.5 µm) in terms of central corneal thickness. There was also good agreement between AS-OCT and micro-OCT in terms of corneal scar measurements (P > 0.5; correlation coefficient >0.99) LOA lower limit −2.1 µm (95% CI: −2.8 to −1.5 µm); upper limit 1.8 µm (95% CI: 1.1 to 2.4 µm). Our pilot study suggests that this novel in vivo micro-OCT imaging technique was able to measure central corneal thickness and scar thickness in agreement with current AS-OCT techniques.